The Art of Quality Health Science Article Writing for Peer-Reviewed Professional Journals: A Review Article - Shreya Buvariya; M.C. Prasant; Arun G. Krishna; Akshay Kumar Mavani; Gosai Mayurgiri Vilasgiri; Gopal Singh Thakur; Rahul Tiwari (Journal of Pharmacy and Bioallied Sciences)
Navigating the intricacies of writing a peer-reviewed medical article demands meticulous adherence to guidelines and an acute understanding of the publication process. This discourse provides a comprehensive overview, emphasizing the crucial components requisite for a successful publication. Delving into the structuring nuances, it delineates the essential elements spanning from title formulation to conclusion drafting. The significance of adherence to journal-specific guidelines, avoidance of plagiarism, and recognition of impact factors are underscored. Furthermore, it elucidates the distinct sections of a medical article, including Introduction, Materials and Methods, Results, and Discussion, elucidating their roles in conveying research findings effectively. Notably, it expounds on the diverse types of health science articles, ranging from original research to systematic reviews, delineating their unique characteristics. Moreover, insights into indexing criteria and impact assessment metrics, such as h-index and journal impact factor, are provided, elucidating their implications for publication success. Finally, common reasons for article rejection and strategies for enhancing publication prospects are discussed, underscoring the evolving landscape of evidence-based medical writing.